Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 2001)
This issue of Networks focuses on teacher research carried out by university teachers and teacher educators. In these articles, instead of carrying out research 'on' teachers - as university researchers have traditionally done - the authors turn the spotlight onto their own practice, investigating the manner in which they play out their roles and responsibilities as teachers of teachers. As each of these authors recognizes, if teacher educators are urging teachers to be reflective practitioners who carry out inquiries in order to improve and better understand their practice and the context in which it takes place, they themselves should 'walk the talk.' Here,then, are a number of investigations of becoming and being a teacher educator in reflective mode.